Concentrations of POPs based wood preservatives in waste timber from demolished buildings and its recycled products in Japan. (15th February 2019) - Koyano, Shyusuke; Ueno, Daisuke; Yamamoto, Takashi; Kajiwara, Natsuko
Highlights: POPs were detected in waste timber and recycled products in Japan in 2016–2017. POPs concentrations were under the LPC limits of the Basel Convention. Chlordane concentrations were higher in timber bearer than in timber column. Timber column had little POPs contamination and is suitable for recycling. Separation of timber will reduce POPs levels in recycled products. Abstract: One of the major proportions of recycled persistent organic pollutants (POPs)-containing waste is timber originating from old buildings, utility poles, and cross-arms because POPs-based treatments were once a common means of preserving wood. In 2016 and 2017, we conducted the first survey in Japan on the residue concentrations of chlordanes (CHLs), pentachlorophenol (PCP), pentachloroanisole (PCA), and polychloronaphthalenes (PCNs) in waste timber ( n  = 55) and its recycled products (woodchip, n  = 42; particle board, n  = 3). In the recycled products, the highest concentrations detected were 0.86 mg kg −1 CHLs, 3.0 mg kg −1 PCP, 1.1 mg kg −1 PCA, and 2.6 mg kg −1 PCNs, which were one to two orders lower than the low POP content (LPC) limits for the environmentally sound management of wastes defined under the Basel Convention (50, 100, and 10 mg kg −1, respectively). In the waste timber, which included bearers and columns from demolished buildings, the highest concentrations were 15 mg kg −1 CHLs, 0.20 mg kg −1 PCP, and 0.036 mg kg −1 PCNs, no higher than about 30% of the LPC limit. The concentration of CHLs in timber bearer was significantly higher than those in timber column ( p  < 0.05). Although none of the waste timber or recycled products had concentrations exceeding the LPC limits, one means of ensuring low POP concentrations in recycled products is separating timber bearer from timber column when demolishing wooden buildings, according to the results in Japan. The timber column can be used to produce recycled products and the remaining timber can be used for heat utilization and power generation.